Pengaruh Program Pelatihan, Etos Kerja, dan Kepuasan Kerja terhadap Kinerja Karyawan di PTPN III - Kismoyogi, Kismoyogi; Lubis, Yusniar; Syaifuddin, Syaifuddin (Universitas Medan Area, 2019)
This study aims to determine and analyze the effect of training programs, work ethics, and employee satisfaction on employee performance at the Directors' Office of PT. Perkebunan Nusantara III. This research method uses a quantitative approach, the type of research is a survey. The sample was determined by a simple random sampling method of 92 people. Data collection through questionnaires. Data were analyzed using multiple linear regression. The results showed that partially and simultaneously, the variables of the training program, work ethic and job satisfaction had a positive and significant effect on the performance of employees in the Office of the Directors of PTPN III Medan. The coefficient of determination of 0.515 means that the effect of the training program, work ethic and job satisfaction on changes in employee performance in the Office of Directors of PTPN III Medan is 51.5%.